2008
DOI: 10.1126/science.1150224
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Progenitor Cells Control the Angiogenic Switch in Mouse Lung Metastasis

Abstract: Angiogenesis-mediated progression of micrometastasis to lethal macrometastasis is the major cause of death in cancer patients. Here, using mouse models of pulmonary metastasis, we identify bone marrow (BM)-derived endothelial progenitor cells (EPCs) as critical regulators of this angiogenic switch. We show that tumors induce expression of the transcription factor Id1 in the EPCs and that suppression of Id1 after metastatic colonization blocked EPC mobilization, caused angiogenesis inhibition, impaired pulmonar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
502
0
6

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 594 publications
(529 citation statements)
references
References 20 publications
20
502
0
6
Order By: Relevance
“…However, conflicting evidence has been reported in relation to their contribution to tumour vessel growth (Gao et al, 2008(Gao et al, , 2009, ranging from major (Lyden et al, 2001) to minor contribution (Peters et al, 2005) or no contribution at all (De Palma et al, 2005). Consistently, we were unable to show EPC incorporation into tumour nascent vessels when Kaposilike sarcoma cells were used as an in vivo model, although a small number of EPCs was detected in vessels formed by human-derived tumour endothelial cells.…”
Section: Discussionsupporting
confidence: 60%
“…However, conflicting evidence has been reported in relation to their contribution to tumour vessel growth (Gao et al, 2008(Gao et al, , 2009, ranging from major (Lyden et al, 2001) to minor contribution (Peters et al, 2005) or no contribution at all (De Palma et al, 2005). Consistently, we were unable to show EPC incorporation into tumour nascent vessels when Kaposilike sarcoma cells were used as an in vivo model, although a small number of EPCs was detected in vessels formed by human-derived tumour endothelial cells.…”
Section: Discussionsupporting
confidence: 60%
“…This idea is supported by a recent report by Gao et al [33] who found that although only 12% of the new blood vessels showed incorporation of EPC, blocking EPC mobilization caused severe angiogenesis inhibition and significantly impaired lung tumor progression. Moreover, in the same study, gene expression analysis of EPC revealed up-regulation of a variety of key proangiogenic genes including vascular endothelial growth factor, platelet-derived growth factor, fibroblast growth factor receptor 1, chemokine ligands and receptors.…”
Section: Contribution Of Epc To Mammary Tumor Vascularization In Animsupporting
confidence: 58%
“…It has been shown that ID1 was essential for the metastasis of cancers to the lung in mouse models of cancer (13,18). Studies on cultured cells and mouse models have shown that levels of ID1 correlate with invasive as well as metastatic properties of cancer cells and that transfection of ID1 could make human breast cancer cells significantly more aggressive and metastatic (32).…”
Section: Discussionmentioning
confidence: 99%